Staphylococcus genus - Small practical guide (in Romanian) - Vili Robert Voichi􀜊oiu; Viorel Herman; Degi Janos (Medicamentul Veterinar)
In this review destined for education of specialists in the field is presented a bacterial genus important for human and animal health. The authors try to present, in two chapters and in a didactical way, all about Staphylococcus genus, like: taxonomy, morphology, and structure, coloration, culture and cultural characteristics, biochemical properties and antigenic structure, genetics and the antibiotic resistance, ecology and environmental factors, pathogenicity [extracellular enzymes and staphylococcal toxins]. The second chapter is dedicated to the description of natural infections with staphylococci and their implications in humans and animals [large and small ruminants, pigs, equines, rabbits, dogs, cats and birds], the last part of the chapter being devoted to the Staphylococcal food toxicity description.